Whole metagenome sequencing of cecum microbiomes in Ethiopian indigenous chickens from two different altitudes reveals antibiotic resistance genes - Kumar, H.; Park, W.; Dajeong Lim; Srikanth, K.; Jun-Mo Kim; Xin-Zheng Jia; Han Jianlin; Hanotte, Olivier H.; Park, Jong-Eun; Oyola, Samuel O. (Elsevier, 2020)
We analyzed the whole genomes of cecum microbiomes of Ethiopian indigenous chickens from two distinct geographical zones: Afar (AF) district (Dulecha, 730 m above sea level) and Amhara (AM) district (Menz Gera Midir, 3300 m). Through metagenomic analysis we found that microbial populations were mainly dominated by Bacteroidetes and Firmicutes. We identified 2210 common genes in the two groups. LEfSe showed that the distribution of Coprobacter, Geobacter, Cronobacter, Alloprevotella, and Dysgonomonas were more abundant in AF than AM. Analyses using KEGG, eggNOG, and CAZy databases indicated that the pathways of metabolism, genetic information processing, environmental information processing, and cellular process were significantly enriched. Functional abundance was found to be associated with the nutrient absorption and microbial localization of indigenous chickens. We also investigated antibiotic resistant genes and found antibiotics like LSM, cephalosporin, and tetracycline were significantly more abundant in AF than AM.